Anomalias geofísicas da região de Diamantina (Minas Gerais): significados geológicos, estruturais e tectônicos - João Paulo de Paula Caldas (2019)
The Diamantina region, located in the Espinhaço Range in its southern segment, is an area that has been the object of numerous geological studies, particularly due to the diamond deposits contained in the basal portion of the Espinhaço Supergroup, the main lithostratigraphic unit that sustains the mountain range. One of the relatively little areas no covered by such studies is geophysics. In this sense, the recent aerogeophysical survey carried out by the CODEMIG state company has allowed the application of new methodologies for the understanding of the structural and tectonic framework of this region, whose surface geology is quite characterized. In order to complement the geological knowledge in the subsurface, modern software was applied, such as OASIS MONTAJ and EULDEP, so that with the methodology of the "Euler Deconvolution" on magnetometric data it was possible to make representative three-dimensional models for anomalies selected in depth. Thus, we sought to understand the meaning of magnetometric and radiometric anomalies and to correlate them with the geology established for the region, contributing with already existing proposals of structural and tectonic evolutions. Geophysical deconvolution profiles were generated to perform a comparative with raised points in fields, selected specifically in the places where the magnetometric anomalies were most striking, with depths of up to 1,500m for the former and 1,900 m for the latter, demonstrating its deep roots The information was integrated in a GIS environment, which aided in the interpretations and evaluations of the obtained results. Together with the Euler Deconvolution data, several magnetometric and gamma-spectrophotometric thematic maps were generated that allowed better interpretation and integration of information, considering the Sopa Brumadinho Formation as the main focus of the anomalies The magnetometry facilitated the identification of subsurface structures and also provided results regarding the possible initial generation of the Espinhaço Basin, including a "master" fault, precursory to the older rift phase.